2012
DOI: 10.4315/0362-028x.jfp-11-251
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Staphylococcus aureus Isolates from Retail Chicken Carcasses and Pet Workers in Northwest Arkansas

Abstract: Staphylococcus aureus can be carried on the skin and nasal passages of humans and animals as a commensal. A case of human methicillin-resistant S. aureus infection resulting from contact with pork has been reported. Poultry carcasses are sold at retail with the skin intact, but pork and beef typically are not. Thus, the risk of methicillin-resistant S. aureus human infection from whole raw poultry carcasses may be greater than that of exposure from pork or beef. The objective of this study was to isolate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
4
17
1
Order By: Relevance
“…However, although the cuts may be similar in name, comparisons between the individual items are not made in this study in order to avoid error between the samples. Prevalence of S. aureus on retail pork products from other studies has ranged from 12% to 59.7% (14)(15)(16)(17)(18)(19)(20). Results from this study are similar to those in the other published reports, since S. aureus was found on 45% of pork products in this study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, although the cuts may be similar in name, comparisons between the individual items are not made in this study in order to avoid error between the samples. Prevalence of S. aureus on retail pork products from other studies has ranged from 12% to 59.7% (14)(15)(16)(17)(18)(19)(20). Results from this study are similar to those in the other published reports, since S. aureus was found on 45% of pork products in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies in the United States to detect the presence of MRSA in retail pork and beef have focused primarily on products popular with the consumer (i.e., ground pork and beef, pork chops) (14)(15)(16)(17)(18)(19). In the southern United States, other cuts of pork and beef are regularly available in grocery stores in the area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this reservoir, resistant strains or resistance genes might spread to humans, via the food chain. Data reports have indicated that food-producing animal species, raw poultry and other meat products harbor antimicrobial-resistant, Gram-positive bacteria (2,(12)(13)(14). However, only a few studies have determined the occurrence of antimicrobial resistance and presence of resistance genes, among staphylococci isolated from poultry (6,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, 11 SCCmec types have been reported and are used for the typing of MRSA strains (11). It is suggested that extensive and, often, indiscriminate use of antimicrobial agents, in animal husbandry, might constitute a risk factor in creating an animal reservoir of antimicrobial-resistant bacteria (2,12). From this reservoir, resistant strains or resistance genes might spread to humans, via the food chain.…”
Section: Introductionmentioning
confidence: 99%